2018
DOI: 10.17765/1983-1870.2018v11n3p441-450
|View full text |Cite
|
Sign up to set email alerts
|

Mortalidade Entre Os Portadores De Tuberculose Em Porto Velho (Ro)

Abstract: Descrever a mortalidade entre os pacientes portadores de tuberculose no município de Porto Velho (RO). Estudo epidemiológico descritivo, do tipo transversal e abordagem quantitativa. A população foi constituída por todos os registros dos portadores de tuberculose que foram a óbito durante o tratamento, entre 2010 e 2015, no município selecionado. As variáveis foram analisadas por meio de distribuição de frequência, após atender os preceitos éticos. Verificou-se no Sistema de Informação de Agravos de Notificaçã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 8 publications
2
5
0
11
Order By: Relevance
“…than 40% of deaths occurred among single individuals, in line with other studies. 15,16 Data analysis showed higher mortality in individuals with up to eight years of study, and data found in the present study were in agreement with studies conducted by Santos-Neto 15 , Espíndula 16 , Lindoso 12 and Siqueira 7 , who reported illiteracy or low education in less financially privileged situations as risk factors for incidence and mortality from TB. 18,19 Low educational level can contribute to unfavorable living conditions such as less knowledge and perception of health, less self-care, and late search for health services that increase vulnerability to TB.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…than 40% of deaths occurred among single individuals, in line with other studies. 15,16 Data analysis showed higher mortality in individuals with up to eight years of study, and data found in the present study were in agreement with studies conducted by Santos-Neto 15 , Espíndula 16 , Lindoso 12 and Siqueira 7 , who reported illiteracy or low education in less financially privileged situations as risk factors for incidence and mortality from TB. 18,19 Low educational level can contribute to unfavorable living conditions such as less knowledge and perception of health, less self-care, and late search for health services that increase vulnerability to TB.…”
Section: Discussionsupporting
confidence: 92%
“…12 Most TB deaths identified in this study refer to pulmonary TB, which represents the main transmissible form of the disease. This scenario is like that found in other national studies, such as those by Espíndola 20 in Campo Grande (84.5% of cases) and Siqueira 7 in Porto Velho (78% of cases). Since pulmonary TB is considered as easy to diagnose and of low cost, it is expected that it can be performed at the primary level of care in health services.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…No que diz respeito à faixa etária, raça/ cor autodeclarada parda, baixa escolaridade, identifica-se a semelhança com outros estudos que abordam sobre a população em geral que adoeceram por TB 14,15 , e que não diferem com o perfil encontrado no censo da PSR 12 e nem com os achados evidenciados neste estudo.…”
Section: Resultsunclassified
“…20 The difficulty in organizing health services, as well as the lack of responsibility for professionals to identify vulnerable TB patients for abandonment and weaknesses in longitudinal monitoring, directly influence non-adherence and unfavorable outcomes. 21,22 Therefore, when aiming for effective treatment observance, only providing access to diagnosis and medication regimen are insufficient. The gaps regarding aspects associated with the disease, such as signs and symptoms, form of transmission, side effects and duration of treatment should be identified in early stages of the disease, targeting to reduce the likelihood of abandonment.…”
Section: Discussionmentioning
confidence: 99%